Home and Abroad : International Student Experiences and Graduate Employability - LeBeau, Ling (Journal of Interdisciplinary Studies in Education, 2023)
Home and Abroad: International Student Experiences and Graduate Employability fills a void of international student research by incorporating multiple countries’ higher education contexts and providing a holistic understanding of international student employability on a global scale. It explores the socio-political environment that impacts international students’ career preparation and employment opportunities and makes recommendations for higher education institutions to better support the career development of international students. Educators who work with international students as well as scholars with a research interest on international student success will be able to identify and address the current challenges facing international students’ career preparation through the research findings in the book.